2021
DOI: 10.3126/medphoenix.v6i1.36796
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile, Precipitating Factors and Outcome of Hepatic Encephalopathy in Patients with Liver Cirrhosis

Abstract: Introduction: Hepatic encephalopathy (HE) is characterized by reversible neuropsychological features and is observed with advanced and decompensated cirrhosis of the liver. Patients outcomes and survival depends on clinical presentation, identification of the precipitating factor, early management, and treatment of complications. This study aims to find out the clinical profile of cirrhotic patients with hepatic encephalopathy, their precipitating factors, and clinical outcomes in patients admitted at a tertia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…This is similar to a study done at Manipal College of Medical Sciences and Teaching Hospital, Pokhara, Nepal which also showed gastrointestinal bleeding as the common precipitating factor. 14 However, a study conducted in Hyderabad, India found infection (67%) as the most common factor followed by constipation (49%) and gastrointestinal bleeding (45%). 15 These wide ranges of prevalence may exist because of the variation in diagnostic tests used for HE, and differences in the etiology and severity of HE that may differ based on the geographical location.…”
Section: Discussionmentioning
confidence: 98%
“…This is similar to a study done at Manipal College of Medical Sciences and Teaching Hospital, Pokhara, Nepal which also showed gastrointestinal bleeding as the common precipitating factor. 14 However, a study conducted in Hyderabad, India found infection (67%) as the most common factor followed by constipation (49%) and gastrointestinal bleeding (45%). 15 These wide ranges of prevalence may exist because of the variation in diagnostic tests used for HE, and differences in the etiology and severity of HE that may differ based on the geographical location.…”
Section: Discussionmentioning
confidence: 98%